In vitro models of intestinal epithelium: Toward bioengineered systems. (January 2021) - Creff, Justine; Malaquin, Laurent; Besson, Arnaud
The intestinal epithelium, the fastest renewing tissue in human, is a complex tissue hosting multiple cell types with a dynamic and multiparametric microenvironment, making it particularly challenging to recreate in vitro . Convergence of recent advances in cellular biology and microfabrication technologies have led to the development of various bioengineered systems to model and study the intestinal epithelium. Theses microfabricated in vitro models may constitute an alternative to current approaches for studying the fundamental mechanisms governing intestinal homeostasis and pathologies, as well as for in vitro drug screening and testing. Herein, we review the recent advances in bioengineered in vitro intestinal models.